KEMENANGAN KELAS MENENGAH: KAJIAN STRUKTURALISME GENETIK TERHADAP NOVEL ALICE’S ADVENTURE IN WONDERLAND KARYA LEWIS CAROLL - Tri Arie Bowo (Universitas Aki, 2018)
This study entitled Middle Class Victory: A Genetic Structuralism Study on LewisCaroll’s novel Alice's Adventure in Wonderland aims to reveal the social classdivisions and main ideas in Alice's Adventure in Wonderland novel in relation to theEnglish social class of Victorian age. This study uses the theory of GeneticStructuralism initiated by Lucien Goldmann. Thel analysis result shows that thecharacters, background, and the plot of the novel describe the social class division.The main idea of the novel is the victory of the English middle class of Victorian age.Keywords: Character, Background, Flow, Social Class, Victorian Age